PENGARUH PROFITABILITAS, LIKUIDITAS, DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN (STUDI PADA SEKTOR PERTAMBANGAN) - Bintang Wahyu Prayogo; Mohamad Nabil Tanzil Furqon; M Helmy Setyo Purwanto; Sigiet Rizky Fidiyanto (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the effect of profitability, liquidity, and solvency on company value in the mining sector, especially in three state-owned companies, namely PT. Timah, PT. Bukit Asam, and PT. Antam, during the period 2014 to 2023. Company value is measured using the Price to Book Value (PBV) ratio, while profitability is measured by Return on Assets (ROA), liquidity by Current Ratio (CR), and solvency by Debt to Equity Ratio (DER). The research method used is quantitative with an associative approach, where data is collected through annual financial report documentation. The results of the analysis show that simultaneously, profitability, liquidity, and solvency have a significant effect on company value. However, partially, only liquidity has a negative and significant effect on company value, while profitability and solvency do not show a significant effect. These findings provide important insights for investors and company management in making investment decisions and managing company resources. This study also recommends increasing the number of samples and time periods for further research in order to obtain more optimal results.